PENERJEMAHAN TEKS PAPAN PENGUMUMAN PADA FASILITAS PUBLIK DI JEPANG (Oleh Mahasiswa Semester VI Pendidikan Bahasa JepangFKIP Universitas Riau 2019) - Sulfiani, Ani; Aibonotika, Arza; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract:This study discusses the translation of announcement board texts at public facilities in Japan by VI semester students of Japanese language education FKIP Riau University and the form and equivalence of studenttranslations in translating the announcement board text.This research is a qualitative descriptive study using the theory of Alwi et al. about modality, Nitta's theory of imperative tenses, and Nida on the equivalence of translation.When viewed from theform and equivalent in the text of the announcement board at a public facility in Japan,then there will be found several types of forms and equivalents in translating the notice board text at public facilities in Japan.This study aims to explain how theform of student translation and the equivalence of the source text with the results of student translations using qualitative methods.This makes it easy for students to translate imperative tenses in Japanese.The method used is the translational equivalent method to find the equivalent of Japanese sentence data into Indonesian.from the results of the study there were 300 results of the translation of students in translating the text of the announcement board at a public facility in Japan.From the results of the student's translation, the discovery of various forms used by students in translating the text papa announcement at public facilities in Japan.KeyWords: Imperative Sentences, Announcement Board Text, Modalities And Equivalents